2016
DOI: 10.3390/rs8030218
|View full text |Cite
|
Sign up to set email alerts
|

InSAR Detection and Field Evidence for Thermokarst after a Tundra Wildfire, Using ALOS-PALSAR

Abstract: Abstract:Thermokarst is the process of ground subsidence caused by either the thawing of ice-rich permafrost or the melting of massive ground ice. The consequences of permafrost degradation associated with thermokarst for surface ecology, landscape evolution, and hydrological processes have been of great scientific interest and social concern. Part of a tundra patch affected by wildfire in northern Alaska (27.5 km 2 ) was investigated here, using remote sensing and in situ surveys to quantify and understand pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
(27 reference statements)
0
36
0
Order By: Relevance
“…The annual mean rate (about 1 cm/year in this study) was slower than those found at the Anaktuvuk River Fire on the North Slope, Alaska [ Jones et al ., ; Iwahana et al ., ], or at the thermokarst site in Central Yakutia, Russia [ Fedorov et al ., ], as compared in Table . In the Anaktuvuk River Fire, rates increased from 2–3 cm/year in the first 3 years to over 6 cm/year in the following 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The annual mean rate (about 1 cm/year in this study) was slower than those found at the Anaktuvuk River Fire on the North Slope, Alaska [ Jones et al ., ; Iwahana et al ., ], or at the thermokarst site in Central Yakutia, Russia [ Fedorov et al ., ], as compared in Table . In the Anaktuvuk River Fire, rates increased from 2–3 cm/year in the first 3 years to over 6 cm/year in the following 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[], using airborne Laser Imaging Detection and Ranging (LiDAR), and by Iwahana et al . [], using spaceborne Interferometric Synthetic Aperture Radar (InSAR). However, these studies have had limited spatial or temporal resolution, and therefore there are needs to investigate thermokarst dynamics in various ice‐rich permafrost regions, in order to grasp overall trends of current thermokarst development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is much less seismically or tectonically active than southern Alaska (Plafker and Berg, 1994). There is essentially no published information about vertical motions across Northern Alaska, outside of studies related to permafrost degradation (Iwahana et al, 2016;Jorgenson et al, 2006;Liljedahl et al, 2016;Liu et al, 2010;Osterkamp et al, 2009;Wang & Li, 1999).…”
Section: Settingmentioning
confidence: 99%
“…It was shown that X-, C-and L-Band data exhibit distinct scattering characteristics for the different land cover classes. Results indicate that the L-Band data were more sensitive to the bare ground classes; thus, it is better suited to investigate and monitor ground properties, e.g., soil moisture, or the surface heave and subsidence (via InSAR) caused by the freezing and thawing of the active layer (compare [17,20,21]); especially in sites dominated by shrubs. In contrast, use of short wavelengths (X-and C-Band) is beneficial for characterizing tundra and wetland vegetation.…”
Section: Class Separability and Feature Selectionmentioning
confidence: 99%